Analisis Perbandingan Kinerja Refrigeran R134a dan MC-22 pada AC Split - Mastur; Nana Supriyana; Warso; Sutarno (Accurate: Journal of Mechanical Engineering and Science, 2022)
AC (Air Conditioner) is one of the cooling machines, whose use is currently increasing. One important component that helps cooling the AC (Air Conditioner) is the refrigerant. Refrigerant is a kind of material or substance in the form of liquid and gas which is usually flowed in the refrigeration machine installation. The purpose of this study was to determine the performance (COP), electrical energy consumption, and cooling rate from the use of refrigerants R134a and MC-22. The independent variables in this research are refrigerant R134a and refrigerant MC-22. The dependent variable in this study is COP (Coefficient of Performance), electrical energy consumption, and cooling rate. The control variable in this study was using time variations. The research material is refrigerant R134a and MC-22 The results of this study showed that R134a refrigerant has a better COP value than MC-22 refrigerant, where the COP value at 60 minutes for R134a refrigerant is 8.6 while for MC-22 refrigerant is 8.0. At 60 minutes the use of refrigerant R134a, the electrical energy used is 385.00 W.h. Meanwhile, 60 minutes of the use of refrigerant MC-22, the electrical energy used is 455.40 W.h.